Presenter Communication Style in Event Programs Meet Nite Live From Metro TV - Novraliza, Novraliza; Afandi, Yusuf (El-Rusyd, 2026)
The development of the television broadcasting industry in Indonesia encourages television stations to present innovative program formats to attract audience attention. Metro TV, as one of the news television stations, presents the news talk show program Meet Nite Live, which combines elements of information and entertainment in conveying current issues. This program is hosted by Valentinus Resa, who is known for his relaxed, humorous, and interactive communication style, thus different from the communication style of presenters on other news talk shows that tend to be formal. This study aims to analyze the communication style of the presenters in the program Meet Nite Live and how this communication style affects the delivery of information to the audience. This study uses a qualitative approach with a descriptive analysis method of the program Meet Nite Live. Data were obtained through observations of several program episodes and documentation studies. The results of the study indicate that the communication style of the presenters in this program combines elements of informative communication with an entertainment approach through the use of everyday language, humor, light intonation, and interaction with the audience. This approach makes the delivery of news issues more communicative, easy to understand, and interesting for the audience. Thus, the communication style of the presenters in the program Meet Nite Live can be an effective media communication strategy in packaging news information to be closer to the audience in the modern media era.